Optimization Of Return and Minimize of Portfolio Risk on The LQ-45 Index Using a Single Index Model - Jaya Agus Prastyo; Anita Handayani; Rahmat Agus Santoso (www.amertainstitute.com, 2025)
This purpose of this research is to analyze the optimal portfolio by using single index model as the basic of investment decision in some companies which are included in LQ-45 index and listed in Indonesia Stock Exchange. The data is the annual individual stock prize, the annual dividend share, the interest of Bank Indonesia Certificate (SBI) and the movement of LQ-45. The companies which have been studied are included in LQ-45. Optimal portfolio is portfolio which has excess return to beta (ERB) value which is larger than the value in which the value is the border point (cut-off point C*) which has the last ERB value and it is larger than the value. The result of this research shows that 2 as optimal stocks which has been combined the proportion of fund, portfolio 2 and portfolio 4 are most optimal.